The evaluation and calibration of pressure mapping system for the measurement of the pressure distribution of agricultural tyres - Misiewicz, Paula A.; Blackburn, Kim; Richards, Terence E.; Brighton, James L.; Godwin, Richard (Elsevier, 2015)
The accuracy of a commercial pressure mapping system was evaluated and a number of techniques for the improvement of pressure measurements were developed. These were required in order to use the pressure mapping system in a tyre/surface interaction study which involved determination of the tyre contact pressure distribution on, both, hard and soil surfaces. In the evaluation of the system, the effect of sensor calibration procedures on the accuracy of the system in measuring pressure was investigated. A purpose built pressure calibration chamber was used to calibrate the sensors, which enabled the proprietary built-in calibration system to be evaluated along with a novel calibration procedure employing, both, an individual and multi-point calibration of each sensing element and the rejection of sensing elements that did not conform to the sensitivity of the majority of the sensing elements. These measures reduced the uncertainty in pressure measurements from ±30% to ±4%. Further, evaluation of the compliance of the material was also conducted to enable the sensors to be used for interface pressure measurements between two different surface materials other than those used during sensor calibration. As a result, a procedure for normalising the recorded pressure by adjusting the recorded load output to equal the applied load was established. The improvement of the accuracy of the sensors made it possible for the system to be used to determine the pressure distribution resulting from a range of tyres on a hard surface and in the soil profile.
Keywords: Pressure mapping system; Calibration; Contact pressure; Soil – tyre interactions